Magnitud beban kerugian pemaju dalam pembangunan rumah kos rendah dan sederhana rendah : kajian kes : kawasan Majlis Bandaraya Johor Bahru - Abbas @ Ahmad, S. Zulifahalila (2004)
Even though the government is striving to meet its ambitious target for low cost housing; unfortunately, developer often fails to achieve it. Majority of developers are not interested to develop low cost housing because the risk of loss. The main objective of this research is to identify and evaluate the problems that have contributed the loss of profit to the developers and to measure the magnitude of their losses. The main problems faced by developers in MBJB area are highlighted in this research. However problems encountered by policy maker and occupants of low cost houses are not include in this research. Interviews were conducted to developers to obtain information for this research. Informations were also obtained by reviewing some books, journals, articles and previous researches carried out on low cost housing. From the research carried out, the problems that affecting developers profit are closely related to high cost of development such as construction cost, infrastructure cost and land cost. Based on analysis carried out, developers were facing about 48% loss fiom the total of development cost. The high margin of losses is a burden for developers and thus affecting their interest to develop low cost houses. In the last chapter of this research, four recommendations have been proposed to improve the situation such as flexibility in the authority's requirement; relating the imposition of low cost unit and permits higher densities on more expensive land, providing state land for developers to develop low cost housing, giving incentives for private developers and also providing hnds as subsidies to develop low cost housing.